Presentation Of The Seven Last Words Of Christ Composed By Théodore Dubois By The Medan Glorious Singers Choir - Kartini Ruth Maduma Manalu; Eniman Gea; Mastaria Simanjuntak (LPPM Universitas PGRI Sumatera Barat, 2024)
Cantata BWV 147 Herz und Mund und Tat und Leben (Heart and mouth, deeds and life) by JS Bach is one of the compositions that is often sung, especially the part